66 Cognitive impairment is not associated with 30 day major adverse cardiovascular events in older (75 years) patients presenting with non-st elevation acute coronary syndrome: an evaluation from the icon1 study. (5th June 2017) - Gu, Sophie Zhaotao; Batty, Jonathan; Sinclair, Hannah; Verrasamy, Murugapathy; Bagnall, Alan; Purcell, Ian; Edwards, Richard; Spyridopoulos, Ioakim; Egred, Mohaned; Zaman, Azfar; Ahmed, Javed; Kunadian, Vijay
Abstract : Introduction: Dementia is leading cause of death in the UK and shares many common risk factors with coronary artery disease. The relationship between cognition and major adverse cardiovascular events (MACE) in older patients presenting with non ST elevation Acute Coronary syndrome (NSTEACS) is not known. Aim: To investigate the association of cognitive impairment with 30 day MACE (mortality, hospital readmission with ACS, unplanned revascularisation, stroke and major bleeding events) in older patients presenting with NSTEACS in the ICON1 study. Method: Over a period of 34 months 277 patients 75 years of age, admitted for invasive management of NSTEACS, were enrolled into a multicentre prospective observational study. Cognitive assessment was performed by Montreal Cognitive Assessment (MoCA) test, where a cut-off of 26 is used to determine cognitive impairment. Frailty was assessed using the Fried criteria, where a score of 0 is robust, 1 or 2 is pre-frail and 3 is frail. Results: 251 patients had a MoCA score calculated at presentation (mean±Standard deviation [SD]=25.1±3.3), nearly half of the patients (n=122, 48.6%) had cognitive impairment. The mean age was 81.2±4.0 years (mean± Standard Deviation [SD]). Patients with cognitive impairment were older compared to normal cognition group (82.2±3.9 vs. 80.2±3.9 years, p<0.001), and were frail (36.1% vs. 18.6%, p=0.002). Overall 19 (7.6%) patients reached MACE outcome, the rate of composite adverse outcomes were 6.6% vs. 8.5% (p=0.555) respectively. No patient died at 30 day in the selected cohort and no one had ST elevation myocardial infarction. There was no difference in the occurrence of non ST elevation myocardial infarction (0.8% vs. 0.8%), unstable angina (0.8% vs. 2.3%, p=0.808), unplanned revascularisation (1.6% vs. 1.6%, p=1.0), stroke/Transient Ischaemic Attack (0% vs. 0.8%, p=1.0), and major bleeding (4.1% vs. 3.9%, p=1.0), and readmission with ACS rate (1.6% vs. 3.1%, p=0.684) between the impaired and normal cognition groups respectively. Conclusion: Cognitive impairment is common in patients over 75 years of age with NSTEACS managed invasively. Those with significant impairment are older and frail. Short-term 30 day MACE outcomes are not different between cognition groups in this selected cohort of patients.